The lonely planet story : once while travelling - Wheeler, Tony.; Wheeler, Maureen (Richmond : Crimson, 2008)
This book is unique mix of autobiography, business history and travel book. It traces Tony and Maureen Wheeler's personal story as well as the often-bumpy evolution of their business from its kitchen table startup, right through to the controversial sale to BBC Worldwide 35 later.
Asia Overland.--South-Eas Asia.--Getting Going, Going Broke.--Near Disaster.--More Headaches.--Quiet for a Spell.--First Europe, Then America.--All About Guidebook.--all the trouble in the world.--Other activities.--The BBC and Beyond.
Keywords: WHEELER, TONY, 1946.; WHEELER, MAUREEN; PUBLISHERS AND PUBLISHING; TRAVELERS; LONELY PLANET PUBLICATIONS (FIRM).; TRAVEL; AUSTRALIA